Flexible Endoscopy With Non-invasive Ventilation Enables Clinicians to Assess and Manage Infants With Severe Bronchopulmonary Dysplasia - Soong, Wen-Jue; Tsao, Pei-Chen; Yang, Chia-Feng; Lee, Yu-Sheng; Lin, Chien-Heng; Chen, Chieh-Ho (Frontiers in Pediatrics, 2022)
Objectives Flexible endoscopy (FE) assessed the entire aeroesophageal tract (AET) and subsequent changes in clinical management in infants with severe bronchopulmonary dysplasia (sBPD). Methods This retrospective study investigated on sBPD infants who received FE measurement from 2011 to 2020. FE was supported with noninvasive ventilation (FE-NIV) of pharyngeal oxygen with nose closure and abdominal compression without artificial mask or airway. Data on AET lesions, changes in subsequent management, and FE therapeutic interventions were collected and analyzed. Results A total of 42 infants were enrolled in the study. Two scopes (1.8 mm and 2.6 mm outer diameter) were used. FE analysis revealed 129 AET lesions in 38 (90.5%) infants. Twenty-eight infants (66.7%) presented with more than one lesion. In 35 (83.3%) infants with 111 airway lesions, bronchial granulations (28, 25.2%), tracheomalacia (18, 16.2%), and bronchial granulations (15, 13.5%) were the leading causes. Fifteen (35.7%) infants had 18 esophageal lesions. No significant FE-NIV complications were observed. The FE findings resulted in changes in management in all 38 infants. Thirty-six (85.7%) infants altered respiratory care with pressure titrations (29, 45.3%), shortened suction depth (17, 26.6%), changed endotracheal or tracheostomy tube depth (10, 15.6%), and immediate extubation (8, 12.5%). Twenty-one (50%) infants had 50 pharmacotherapy changes, including steroids, anti-reflux medicine, antibiotics, and stopped antibiotics. Eighteen (42.8%) infants had received 37 therapeutic FE-NIV procedures, including 14 balloon dilatations, 13 laser-plasty, and 10 stent implantations. Seven (16.7%) infants underwent surgeries for four tracheostomies and three fundoplications. Conclusion FE-NIV could be a safe and valuable technique for direct and dynamic visual measurement of AET, which is essential for subsequent medical decision-making and management in infants with sBPD.